Development of the 'Selangkah Mengelilingi Salatiga' (SEMESTA) Board Game to Improve Fourth-Grade Primary School Students’ Problem-Solving Skills in Plane Geometry - Akmal Rizqi Ramadhan; Dani Kusuma (Electronic Journal of Education, Social Economics and Technology, 2025)
This study was motivated by the lack of students’ problem-solving abilities in plane geometry and the limited availability of appropriate learning media. These factors contribute to low learning outcomes in problem-solving and minimal student engagement during the learning process. The development of the Selangkah Mengelilingi Salatiga (SEMESTA) board game aims to address these issues. The study was conducted at SDN Tingkir Lor 02 using a Research and Development (RD) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, validation questionnaires, response questionnaires, pre-tests, and post-tests. Media validation results reached 94.66%, categorized as “Highly Valid,” and material validation scored 69.33%, categorized as “Valid.” The practicality test results were 98.66% from teachers and 73.79% from students, indicating that the media was “Highly Practical.” A significant improvement in problem-solving ability was observed, as indicated by an N-Gain score of 0.6701, categorizing the media as “Moderately Effective,” with the average pre-test score rising from 42.93 to 78.79 in the post-test. It can be concluded that there is a significant difference between the pre-test and post-test results, and thus, the SEMESTA board game is suitable for use in the learning process.